The Perspectives of Mathematics Pre-Service Teacher Student Toward the Use of Educational Games in Mathematics Learning - Nilza Humaira Salsabila; Ulfa Lu'luilmaknun; Ratih Ayu Apsari; Nourma Pramestie Wulandari; Sripatmi Sripatmi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
Abstract. The purpose of this study was to determine the perspective of mathematics education college students or preservice mathematics teachers on the use of educational games in mathematics learning at schools. This research is a descriptive study with a quantitative approach. The research subjects were 48 college students in mathematics education. Student perspective data were obtained through a questionnaire given, then the data were tabulated and analyzed. The results showed that 93.75% of students agreed with the use of games in learning mathematics. The reasons students agree with the use of games are students become interested in learning, learning becomes fun, students do not get bored, game technology needs to be utilized in learning activities, the topic is easy to understand, students can learn while playing, games can increase learning interest, learning becomes not monotonous, students become enthusiastic about learning, current learning must be more modern, students are not surfeited about learning, games are following the current digital era, can be a media of learning, effective in learning, increase students' creative thinking, reduce the negative effects of handphone, students become challenged, and students are more relaxed to learn. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui perspektif mahasiswa pendidikan matematika atau calon guru matematika terhadap penggunaan game edukasi pada pembelajaran matematika di sekolah. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Subjek penelitian merupakan mahasiswa pendidikan matematika yang berjumlah 48 mahasiswa. Data perspektif mahasiswa diperoleh melalui angket yang diberikan, kemudian data ditabulasi dan dianalisis. Hasil penelitian menunjukkan bahwa 93,75% mahasiswa setuju dengan penggunaan game pada pembelajaran matematika. Alasan mahasiswa setuju dengan penggunaan game adalah siswa menjadi tertarik pada pembelajaran, pembelajaran menjadi menyenangkan, siswa tidak bosan belajar, teknologi game perlu dimanfaatkan dalam kegiatan pembelajaran, materi mudah dipahami, siswa dapat belajar sambil bermain, game meningkatkan minat belajar, pembelajaran menjadi tidak monoton, siswa menjadi semangat belajar, pembelajaran sekarang harus lebih modern, siswa tidak jenuh belajar, game sesuai dengan zaman digital sekarang, dapat menjadi media pembelajaran, efektif pada pembelajaran, meningkatkan pemikiran kreatif siswa, mengurangi efek negatif handphone, siswa menjadi tertantang, dan siswa lebih santai belajar.